Evaluation of the loading capacity and patterns of packaged DNA in AAV genomes of different sizes using long-read sequencing - Mitsuki Kosaka; Ai Fujita Sajiki; Kosuke Fujita; Kazuhisa Yamada; Kenichi Kawano; Kiichi Hirazawa; Tsuyoshi Matsuno; Masahiko Takada; Nobuhiro Shimozawa; Ken-ichi Inoue; Kenya Yuki; Koji M. Nishiguchi (Molecular Therapy: Methods & Clinical Development)
The loading capacity of adeno-associated virus (AAV) vectors is reportedly 4.7–5.0 kb, which limits the size of genes that can be treated with gene therapy. However, the effects of oversized genomes on the integrity of packaged AAV genomes are poorly understood. Herein, nanopore long-read sequencing was used to evaluate genomic integrity in AAV vectors harboring genomes of various sizes. AAV had a reduced proportion of full-length genomes at a vector length of 4.9 kb, which declined rapidly between 4.9 and 5.0 kb. This was mainly attributable to defects in genome packaging rather than genome synthesis. Furthermore, the pattern of packaged DNA was unique to the arrangement of the components of the oversized genome. However, an 86.3% reduction in the proportion of full-length genomes (4.7 vs. 5.0 kb) was not consistent with the retained expression of the reporter gene in the mouse retina. This discrepancy might be partially attributable to the preferential inclusion of the region containing the reporter gene. These results highlight the utility of long-read sequencing in assessing the genomic integrity and design of AAV vectors, as the pattern of packaged genomes appears to be unique to each vector, particularly for oversized AAV genomes.